Role of religious beliefs in adherence to antiretroviral therapy in the Cape Town metropole: a study protocol - Ferdinand C Mukumbang; Anam Nyembezi; Ivo Nchendia Azia; Shernaaz Carelse (BMJ Open, 2022)
Introduction There are presently over four million people living with HIV (PLHIV) in the South African national antiretroviral therapy (ART) programme. However, some ART programmes are battling poor ART adherence emanating from patient-related factors, including their religious beliefs. In this paper, we outline a study protocol to understand the adherence behaviours of Pentecostal Christians living with HIV to ART and to develop guidelines that can be used to strengthen ART adherence.Methods and analysis We propose an exploratory multimethod research design. In phase 1, a scoping review will be conducted. The data captured in this phase will be put into charting forms, analysed qualitatively, and then collated and summarised to hypothesise the relationship between religious beliefs and ART adherence. In phase 2, an explanatory qualitative approach will be used. Semistructured interviews will be conducted with purposefully selected religious leaders, Pentecostal Christians living with HIV who are not adhering to ART and healthcare workers delivering ART at selected healthcare facilities in the Milnerton subhealth district. The qualitative data obtained in this phase will be transcribed verbatim and analysed thematically using the ATLAS.ti V.8 software program towards strengthening the hypothesised relationship between religious beliefs and ART adherence. In phase 3, intervention mapping and nominal group techniques will be applied with purposefully selected stakeholders to develop guidelines to strengthen ART adherence among PLHIV.Ethics and dissemination Phase 1 of the study will not require ethics approval. Ethics approval for phases 2 and 3 has been received from the University of the Western Cape Biomedical Research and Ethics Committee and the Western Cape Department of Health. Informed consent forms will be obtained from all participants at the different phases of the study. The study findings will be disseminated through publications in scientific journals, presentations at conferences and workshops aimed at improving ART adherence.